Assessing the Empirical Linkage Among Access to Finance, Firm Quality, and Firm Performance: New Insight From Bangladeshi SMEs’ - Chowdhury, Mohammad Abir Shahid; Chuanmin, Shuai; Sokolová, Marcela; Akbar, Ahsan; Ali, Zahid; Ali, Hussain; Alam, Md. Zahid (Frontiers in Psychology, 2022)
Access to finance plays a central pillar on sustainable firm growth of developing and developed nations. This study depicts the linkage between access to external finance, firm quality, and firms’ performance as measured by labor productivity for sustainable SMEs’ development by employing the OLS regression and propensity score matching (PSM) techniques to alleviate the selection bias and endogeneity issue on Word bank enterprise survey (WBES) cross-sectional firm-level data of 3196 Bangladeshi SMEs’ for 2007-2013 period. Empirical evidence linking access to external finance and labor productivity has been positive and significant. There is, however, our finding explores a negative but significant relationship between exports and SME labor productivity. A further look into the results also exhibits no statistical significance in the interaction effect between firm quality and access to finance on labor productivity. Moreover, the study anticipates novel empirical support that, the disintegration effect of export sales between direct and indirect exports with labor productivity for credit-accessed firms, is also found statistically insignificant. Then several policies are drawn from the results to gain international competitiveness, and to ensure more external finance channels for enhancing SMEs’ performance and sustainable firm growth.